Regional identity: The Role of the Czech Republic and Poland in maintaining Sorbian identity - Barçon, Maëla (Jihočeská univerzita, 2021)
This master thesis focuses on the Sorbs, a small Slavic minority living in Lusatia, Germany. The Sorbs are only 60 000, and their identity is currently threatened. This research aims at knowing to what extent the Czech Republic and Poland, as Slavic neighbours, can help the Sorbs maintain their identity. 6 semi-structured interviews were conducted with Sorbian, Czech, and Polish people. Several topics were addressed: the Sorbian identity, the personal experiences with the Czech Republic and Poland, the Sorbian-Czech and Sorbian-Polish relations as well as the Sorbs' relations with Germany. The results show that Sorbian identity is highly threatened and provide a state of play of the current Sorbian-Czech and Sorbian-Polish relations. Finally, the role that the Czech Republic and Poland could have in maintaining Sorbian identity in the coming years was discussed.
Regional identity: The Role of the Czech Republic and Poland in maintaining Sorbian identity
Keywords: minority; the Sorbs; Lusatia; Sorbian identity; identity preservation; Germany; the Czech Republic; Poland; historical relations; Slavic culture and languages.; minority; the Sorbs; Lusatia; Sorbian identity; identity preservation; Germany; the Czech Republic; Poland; historical relations; Slavic culture and languages